Teoretska opredelitev in vloga dramatike v jezuitskem redovnem ustroju - Deželak Trojar, Monika (Primerjalna književnost, 2020)
The article deals with the phenomenon of Jesuit drama, which covers all of the dramatic activity of the Jesuits within their colleges, both adaptations of older (ancient and humanistic) dramatic texts and their own original dramas, including both school and religious performances, regardless of the place of performance (auditorium, classroom, school hall, church, school yard, street, etc.). The first part focuses on the definition of Jesuit drama, as can be deduced from the fundamental documents of the Jesuit order: The Founding Documents of the Society of Jesus, The Constitutions of the Society of Jesus, The Plan and Regulation of Study of the Society of Jesus, and The Rules of the Society of Jesus. The article then presents the main theorists of Jesuit drama from the beginnings of the order to its dissolution (Jakob Pontanus, Martin Delrio, Antonio Possevino, Alessandro Donati, Jakob Masen, Athanasius Kircher, Nicolaus Avancini, Claude-François Menestrier, Franz Lang in Franz Neumayr), their general point of departure in ancient dramatic theory, and their reliance on the humanistic school and medieval religious drama. It demonstrates the adaptation of these models to Jesuit educational, didactic and catechetical needs, as well as to the spirit of the time in which Jesuit drama originated and developed. Attention is drawn to the main feature of Jesuit drama, the desire to influence the senses of the audience, which is reflected in the Jesuit%s fondness of audiovisual effects, emblems, symbols, personifications and allegories. At the same time, the article emphasises that the spiritual foundation of this understanding of drama must be sought in the Spiritual Exercises of St Ignatius of Loyola, the founder of the order. In these exercises, the deterrence of people from sin and the promotion of virtue are emphasised as the main goals of the Jesuit order.
Keywords: Avstrijska jezuitska provinca; dramska poetika; duhovna drama; jezuiti; jezuitska drama; Jezuitski kolegij v Ljubljani; jezuitsko gledališče; književnost in religija; krščanska književnost; perioha